2005
DOI: 10.1007/s00264-004-0613-7
|View full text |Cite
|
Sign up to set email alerts
|

Giant cell tumors of the knee: subchondral bone integrity affects the outcome

Abstract: From January 1992 to July 2001, we treated 38 patients with giant cell tumour in the knee region. Seventeen tumours were located in the distal femur and 21 in the proximal tibia . Twenty patients were classified as Campanacci grade II, 15 as grade III, and three as grade I. Patients' mean age was 34.5 (19-65) years, and the mean follow-up was 52 (24-134) months. Operative procedures were chosen according to the extent of bone and soft-tissue involvement. In 28 patients, intralesional curettage and bone graftin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 17 publications
5
50
0
Order By: Relevance
“…There were three patients with Stage 1 lesions, 45 patients with Stage 2 lesions and 32 patients with Stage 3 lesions. Average subchondral involvement by the tumour was 27.5% (range: 15-89%) according to the method of Chen et al [5]. The Campanacci staging did not show a significant correlation with degenerative changes at any of the time points in the follow-up (p>0.05).…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…There were three patients with Stage 1 lesions, 45 patients with Stage 2 lesions and 32 patients with Stage 3 lesions. Average subchondral involvement by the tumour was 27.5% (range: 15-89%) according to the method of Chen et al [5]. The Campanacci staging did not show a significant correlation with degenerative changes at any of the time points in the follow-up (p>0.05).…”
Section: Resultsmentioning
confidence: 84%
“…The area of affected subchondral bone was measured on anteroposterior and lateral radiographs. The subchondral bone was defined as affected when the distance between it and the tumour was less than 3 mm [5]. The GCTs were staged according to the system described by Campanacci et al [3]: stage 1 lesions were intraosseus, stage 2 lesions were intraosseus lesions with cortical thinning and stage 3 lesions extended extraosseously.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Errani et al [10] found mean MSTS scores of 92% and 94% for patients treated with two adjuvants versus three adjuvants, respectively. Chen et al [6] found mean MSTS scores of 88% in patients who underwent intralesional curettage.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment depends upon the stage according to the Campanacci grade. 6 With more involvement of subchondral bone, 2 the functional outcome is generally worse after treatment. Custom mega Prosthesis as the primary modality 1 in the management of malignant bone tumours of the lower limb is seen to have superior results with minimal complications.…”
Section: Introductionmentioning
confidence: 99%